1999
DOI: 10.1002/(sici)1097-0029(19991015)47:2<135::aid-jemt6>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Actin cytoskeleton in plants: From transport networks to signaling networks

Abstract: The plant actin cytoskeleton is characterized by a high diversity in regard to gene families, isoforms, and degree of polymerization. In addition to the most abundant F‐actin assemblies like filaments and their bundles, G‐actin obviously assembles in the form of actin oligomers composed of a few actin molecules which can be extensively cross‐linked into complex dynamic meshworks. The role of the actomyosin complex as a force generating system — based on principles operating as in muscle cells — is clearly esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
78
0
5

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(84 citation statements)
references
References 390 publications
(421 reference statements)
1
78
0
5
Order By: Relevance
“…However, to date there has been no definitive description of the mechanism that senses the position or movement of amyloplasts within the statocytes (Perrin et al, 2005). It has been proposed that sedimenting amyloplasts may trigger mechano-sensitive ion channels at the plasma membrane or ER, either directly, by sedimentation onto them (Sack, 1991;Zheng and Staehelin, 2001), or indirectly, by exerting pressure on the actin cytoskeleton (Sievers et al, 1989;Volkmann and Baluska, 1999) or disrupting its meshwork upon sedimentation (Yoder et al, 2001). The latter model may have to be reconsidered in light of studies indicating that low concentrations of the actin-depolymerizing drug latrunculin B enhance gravitropism rather than inhibiting it (Hou et al, 2003(Hou et al, , 2004Yamamoto and Kiss, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…However, to date there has been no definitive description of the mechanism that senses the position or movement of amyloplasts within the statocytes (Perrin et al, 2005). It has been proposed that sedimenting amyloplasts may trigger mechano-sensitive ion channels at the plasma membrane or ER, either directly, by sedimentation onto them (Sack, 1991;Zheng and Staehelin, 2001), or indirectly, by exerting pressure on the actin cytoskeleton (Sievers et al, 1989;Volkmann and Baluska, 1999) or disrupting its meshwork upon sedimentation (Yoder et al, 2001). The latter model may have to be reconsidered in light of studies indicating that low concentrations of the actin-depolymerizing drug latrunculin B enhance gravitropism rather than inhibiting it (Hou et al, 2003(Hou et al, , 2004Yamamoto and Kiss, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacological and genetic studies suggest its role in a variety of cellular processes such as organelle movement, guard cell movement, cell polarity development, po-larized cell growth, and cell division (Volkmann and Baluska, 1999;Belanger and Quatrano, 2000;Vantard and Blanchoin, 2002). Using live markers such as green fluorescent protein (GFP; Kost et al, 1998) fused to the actin-binding domain of the mouse talin and phalloidin staining in fixed cells, different types of actin structures have been observed in plant cells (Szymanski et al, 1999;Hepler et al, 2001;Frank and Smith, 2002).…”
mentioning
confidence: 99%
“…Microtubules and actin filaments (AFs) are dynamic structures and play integral roles in the architecture of cells (Volkmann and Baluška 1999;Staiger et al 2000;Wasteneys 2002) and in the processes of cell division, cell expansion, intracellular transport and morphogenesis in plants (Straight and Field 2000;Verma 2001;Stoeckel and Takeda 2002;Lloyd and Chan 2004). The MT cytoskeleton is present in four distinct arrays: (1) The pre-prophase band (PPB), marking the future division site, (2) the mitotic apparatus, segregating the chromosomes, (3) the phragmoplast, involved in producing the cell plate, and (4) the interphase cortical MT array, involved in cellulose-microfibril deposition in the cell wall (Giddings and Staehelin 1991;Goddard et al 1994).…”
Section: Introductionmentioning
confidence: 64%
“…Because the accessibility for tubulin and actin epitopes was the same, it is suggested that, despite the application of MBS ester, the preservation of the AFs or their epitopes was inferior. It was indeed reported that AFs are very difficult to preserve especially at the ultrastructural level (Hepler et al 1993;Staehelin and Hepler 1996;Volkmann and Baluška 1999). Thus, further protocol development is necessary.…”
Section: Discussionmentioning
confidence: 99%